54.2k views
1 vote
Multiple choice

I genuinely have no idea-- but I don't think it's the first one or the last.
I think it may be the third one but I'm not too sure.

Multiple choice I genuinely have no idea-- but I don't think it's the first one or-example-1
User Asun
by
4.6k points

1 Answer

10 votes

Answer:

The correct option is;

By first reversing Reaction 2 and then adding the enthalpy of Reaction 1 and the enthalpy of reaction 2

Step-by-step explanation:

The given reactions are;

1) C₂H₂ (g) + 2H₂ (g) → C₂H₆ (g)
{} ΔH = -75 kcal

2) C₂H₄ (g) + H₂ (g) → C₂H₆ (g)
{} ΔH = -33 kcal

3) C₂H₂ (g) + H₂ (g) → C₂H₄ (g)
{} ΔH = ?

By reversing reaction (2) and subtracting the reactants from the products we then have followed by adding the enthalpy of reaction 1 to the value of the enthalpy of the (reversed) reaction 2, we have;

C₂H₂ (g) + 2H₂ (g) → C₂H₆ (g)
{} ΔH = -75 kcal

C₂H₆ (g) → C₂H₄ (g) + H₂ (g)
{} ΔH = 33kcal

Adding, and cancelling out the italicized terms which are repeated in the product and reactants, we get

C₂H₂ (g) + H₂ (g) → C₂H₄ (g)
{} ΔH = -75 kcal + 33 kcal = -42 kcal

Therefore, the correct option is "by first reversing Reaction 2 and then adding the enthalpy of Reaction 1 and the enthalpy of reaction 2"